2008
DOI: 10.1111/j.1872-034x.2008.00357.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial splenic embolization prior to combination therapy of interferon and ribavirin in chronic hepatitis C patients with thrombocytopenia

Abstract: The increase of platelet counts after PSE may allow the safe use of IFN and RBV and improve the SVR rate in chronic hepatitis C patients with thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 25 publications
2
40
1
2
Order By: Relevance
“…To date, several papers on the efficacy of PSE prior to starting interferon therapy have been already reported (12)(13)(14)(15)(16). First, Moreno et al (12,13) reported the usefulness of PSE prior to starting the combined therapy with peginterferon and ribavirin in HCV cirrhotic patients with thrombocytopenia; however, their reports were one-arm studies and did not have a non-PSE group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several papers on the efficacy of PSE prior to starting interferon therapy have been already reported (12)(13)(14)(15)(16). First, Moreno et al (12,13) reported the usefulness of PSE prior to starting the combined therapy with peginterferon and ribavirin in HCV cirrhotic patients with thrombocytopenia; however, their reports were one-arm studies and did not have a non-PSE group.…”
Section: Discussionmentioning
confidence: 99%
“…First, Moreno et al (12,13) reported the usefulness of PSE prior to starting the combined therapy with peginterferon and ribavirin in HCV cirrhotic patients with thrombocytopenia; however, their reports were one-arm studies and did not have a non-PSE group. Furthermore, although the currently recommended therapy of chronic HCV infection is the combination of peginterferon and ribavirin (5), the study population of other 2 reports mainly consisted of patients treated with conventional interferon or consensus interferon (14,15). Thus, until recently, few comparative studies of the efficacy of PSE prior to starting the combined therapy with peginterferon and ribavirin in chronic hepatitis C patients with thrombocytopenia have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have a relatively high proportion of severe end stage patients desiring intensive care. Although splenectomy and arterial splenic embolization are efficient methods for treating HCC patients with severe thrombocytopenia [7][8][9][10], these treatment options are not always available for patients with advanced liver cirrhosis. Thus, severe thrombocytopenia is still a major unresolved issue affecting HCC treatment, and eltrombopag, a thrombopoietin-receptor agonist, is expected to improve HCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, thrombocytopenia is an important factor that can interfere with clinical treatments in patients with chronic liver diseases. Splenectomy or partial splenic embolization is generally considered an effective therapeutic approach for thrombocytopenia [7][8][9][10]. However, these therapeutic procedures are invasive and are not always an option for patients with advanced chronic liver diseases like liver cirrhosis.…”
Section: Introductionmentioning
confidence: 99%
“…After PSE, the blood flow of the splenic vein decreases because of a decrease of the blood flow of the splenic artery ; thus, portal hypertension is improved by this procedure. There have been recent reports of PSE performed for pancytopenia prior to hepatocellular carcinoma treatment and interferon therapy for hepatitis C virus infection 11,12) . However, platelet transfusions are often required prior to PSE, as patients with CLD often develop thrombocytopenia due to hypersplenism.…”
Section: Casementioning
confidence: 99%